Project Based Learning: Using Digital Storytelling to Improve Generation Z Students’ Botanical Literacy in Botanical Course - Anggarani, Dinar Arsy; Sari, Murni Sapta; Sulisetijono, Sulisetijono (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to examine the effectiveness of implementing PjBL combined with DS in enhancing botanical literacy among biology students. This research follows a quasi-experimental non-equivalent control group design. The botanical literacy scores of students are normally distributed, and the data variance is homogeneous (sig>0.05). The findings indicate that the implementation of Project-Based Learning (PjBL) supported by digital storytelling can improve students' botanical literacy. The results of the LSD (Least Significant Difference) post-hoc test show no significant difference between the experimental group using PjBL with digital storytelling and the control group using PjBL without digital storytelling. There is an indication that the use of artificial intelligence (AI) in answering post-test questions may have influenced the research results. Nonetheless, digital storytelling remains a promising innovative approach in botany education. Its advantages during the learning process are evident in students' higher engagement, increased creativity in presenting material, and its ability to visualize complex botanical concepts effectively. Further integration of other technologies in learning is necessary, along with stricter control over AI usage during assessments.